River flooding in a changing climate: rainfall-discharge trends, controlling factors, and susceptibility mapping for the Mahi catchment, Western India - Das, Sumit; Scaringi, Gianvito (Natural hazards (Dordrecht), 2021)
The Mahi—one of the major rivers in Western India—is subject to frequent major flooding, which severely affects the local economy and infrastructure. Little has been done, however, to assess the flood patterns and severity along its course. Here, the Mann–Kendall and Pettitt tests are used to identify long-term trends of precipitation and peak streamflow at multiple locations in the catchment. Then, flood susceptibility mapping is performed by the analytical hierarchy process, accounting for 14 geomorphic, hydraulic, and geologic factors. The analyses suggest a decline in total precipitation and peak flow discharges at most locations, consistently with the general climatic trend of the area, featuring a weakening summer monsoon. Nonetheless, a significant portion of the catchment area remains highly susceptible to flooding, with stream powers capable of mobilizing boulders up to 1 m in size in extraordinary floods. These results can support the work of engineers and policymakers dealing with floods in the study area, but the proposed methodology can also be applied to other fluvial catchments to evaluate the role of climate trends in modulating flood susceptibility.